Ultra-shallow fluorine implantation from r.f. plasma as a method for improvement of electro-physical properties of MIS structures with PECVD gate dielectric layers - Kalisz, M.; Mroczynski, R. (International Conference on Plasma Surface Engineering, 2013)
In this work a comprehensive analysis of changes in electrical and reliability parameters, which are introduced by the presence of a fluorine-rich layer in the gate structure based on MOS (Al/SiO2/Si) and MIS (Al/SiOxNy/Si) system, has been carried out. The surface of silicon substrates prior to the test structure execution was subjected to the processes of ultra-shallow ion implantation from CF4 plasma, different, than those usually found in the literature. To this end, the conventional plasma reactors were utilized to carry out a plasma enhanced chemical vapour deposition process PECVD and reactive ion etching RIE. To perform gate dielectric layers the PECVD method was used. The conducted analysis of the electrical properties was complemented by spectroscopic measurements (SIMS), which allowed the identification of causes and effects of observed changes in electro-physical parameters.